Similarity Effect and Purchase Behavior of Organic Food Under the Mediating Role of Perceived Values in the Context of COVID-19 - Liu, Chunnian; Zheng, Yan; Cao, Dayu (Frontiers in Psychology, 2021)
Due to the influence of COVID-19, people pay more attention to the balance between human and nature and pursue more healthy, environmental and nutritional sustainable products (such as organic food). However, the mainstream consumption of organic food is far less, especially in developing countries like China. Therefore, it is urgent to take effective measures to promote the development of China’s organic food market. This current study investigated the relationships between consumers’ similarity (i.e. information anxiety, uncertainty, sustainable consumption attitude), perceived values (i.e. functional value, health value and environmental value) and organic purchasing behavior based on the Stimulus-Organism-Response (S-O-R) theoretical model and information similarity effect. And considering gender differences in consumers’ similarity, perceived values and organic purchasing behavior. Meanwhile, the mediating effects of perceived values on the relationship between consumers’ similarity and purchasing behavior were also discussed, considering the background of COVID-19. Data were collected using structured questionnaire survey in first-tier cities in China. A total of 344 consumers of organic foods participated in the study. Structural equation modelling was employed for data analysis. The results indicated the significant association of information anxiety, uncertainty and sustainable consumption attitude with perceived values. And perceived values and sustainable consumption attitude had a positively significant influence on purchase behavior. In addition, environmental value played mediating effects in the relationships between organic purchasing behavior and information anxiety, uncertainty and sustainable consumption attitude. And the impact of sustainable consumption attitude and environmental value on organic purchasing behavior differed in gender. The research not only provides novel insights for understanding organic consumption, but also provides reference for organic sellers to develop sales strategies and policy makers to formulate policies to guide organic consumption, which are conducive to promoting China’s organic food industry.